AN UNUSUAL CASE OF PROGRESSIVE CEREBELLAR ATAXIA. Issue 11 (9th October 2013) - Chhetri, Suresh Kumar; Majeed, Tahir; Dick, Jeremy; Taylor, AMR; Ealing, John
Abstract : Introduction: Ataxia with oculomotor apraxia type 2 (AOA2) is an autosomal recessive disorder due to mutations in the senataxin gene resulting in progressive cerebellar ataxia, peripheral neuropathy and occasional oculomotor apraxia. 1 Approximately 96% of the patents have raised serum alpha fetoprotein (AFP) levels. 1 We present a patient presenting with ataxia and choreoathetosis, secondary to AOA2, whose serum AFP level was at the upper limit of normal range. Case presentation: A 17 year old college student, born of non–consanguineous parents, presented with a 5 year history of gradual onset, progressive impairment of co–ordination. He also reported gradual decline in his academic performance. There was no history of seizures, visual, bulbar or sphincter disturbances. He was a non–smoker and had no history of alcohol or drug abuse. Past medical and family history was unremarkable. Clinical examination demonstrated mild bradyphrenia and a subtle ataxic dysarthria. Cranial nerves were normal. Limb tone and power were unremarkable. Reflexes were normal in the upper limbs but knee jerks were reduced and ankle jerks were absent bilaterally. Plantars were downgoing. There was mild blunting of pinprick distally over the legs. His gait was mildly ataxic, more pronounced with tandem walking. Choreoathetoid movements were noted in his hands. The following investigations were either normal or negative: haematological, biochemical and copper studies, lipid profile, serum electrophoresis, creatine kinase, autoimmune screen, white cell enzymes, mitochondrial studies, vitamin E levels, acanthocytes, ataxia telangiectasia (A–T) and spino–cerebellar ataxia mutations. Genetic study for Friedreich's ataxia was negative. AFP level was 10 (normal range <10 kU/l). Electroneuromyography showed evidence of generalised axonal motor and sensory neuropathy. Magnetic resonance imaging of the brain revealed mild cerebellar atrophy. Further review at 6 months demonstrated evidence of mild oculomotor apraxia. Molecular genetic testing revealed compound heterozygous mutations in the senataxin (SETX) gene, resulting in loss of senataxin protein, confirming the diagnosis of AOA2. Conclusion: Oculomotor apraxia, although included in the acronym, is not obligatory for diagnosis of AOA2. A range of movement disorders including tremor, chorea and dystonia may be present in approximately 14% of the patients. 1 AFP level may occasionally be in the upper range of normal and may increase with time. AFP is an important biomarker for recessive ataxias and should be included in the investigation of recessive cerebellar ataxias or adolescent movement disorders of unknown aetiology.